Experiences with the use of a single ox for cultivation in the Ethiopian highlands - Astatke, A.; Mohamed-Saleem, M.A. (Nitrogen Fixing Tree Association, 1994)
Tests on the use of a single ox with a modified maresha plow were carried out in Ethiopia at the International Livestock Centre for Africa (ILCA) Debre Berhan station, on farmers' fields at Debre Zeit, and on a test track at the Agricultural Implement Research and Improvement Centre (AIRIC) near Nazareth. The power developed by a single local zebu animal using the V-yoke was 0.3 kW under field conditions and varied between 0.15 and 0.19 kW on the test track; a pair of oxen is capable of producing 0.4 kW. In 1985 the ox/seed project was started in the Ankober and Seladengay Woredas of Northern Shoa Province to help drought victims. A total of 1800 farmers were each supplied with an ox, grain seed, a modified maresha and a V-yoke. There were problems with disseminating the use of single oxen in these areas. Extension of the technology was made difficult by the physical environment (steep slopes, high percentage of stone cover and hard soils) and by the farmers' negative social attitude towards the technology. Also, the farmers were not given adequate training in the use of the single ox with the modified maresha. The adoption rate of the technology was therefore low.